Strategy of combining offline 2D LC‐MS with LC‐DIA‐MS/MS to accurately identify chemical compounds and for quality control of Dioscorea septemloba Thunb. Issue 7 (16th July 2022) - Chen, Hongxi; Wang, Lei; Wang, Chenxi; Zhang, Yi; Yu, Haiyang; Fu, Zhifei; Fu, Xuebin; Han, Lifeng
Abstract: Introduction: Dioscorea septemloba Thunb. (DST), the rhizome of Dioscorea spongiosa J. Q. Xi, M. Mizuno et W. L. Zhao or Fuzhou Dioscorea futschauensis Uline ex R. Kunth, has multiple biological activities. Objectives: We aimed to comprehensively characterize the chemical composition of DST and develop a quality control method. Methods: Based on a UHPLC/Q‐Orbitrap‐MS platform, we developed an offline 2D LC‐MS method (HILIC×RPLC) to characterize the chemical constituents in the 75% ethanol extract of DST at first. Secondly, a data‐independent acquisition mode (DIA) was further established to conduct rapid qualitative analysis of compounds in DST from different habitats. Then, six differential compounds were screened out and selected as quantitative markers by UPLC‐QQQ‐MS to evaluate the content of DST from different habitats. Results: In total, 137 compounds were identified in DST by combining offline 2D LC‐MS with LC‐DIA‐MS/MS. Then, simultaneous targeted/non‐targeted scanning technology was established based on the precursor ion list. Finally, six compounds, including dioscin, gracillin, pseduoprotodioscin, pseudoprotogracillin, protodioscin, and protogracillin, were accurately determined. The method validation showed a good linear relationship in the concentration range investigated ( R 2 > 0.999). The average recovery ranged from 86% to 107.5%, and LOD and LOQ were between 0.01 and 0.40 μg·mL −1 . Conclusion: Our strategy integrating offline 2D LC‐MS and the DIA mode could effectively separate and identify compounds from DST, indicating it can be used in subsequent compounds characterization studies. At the same time, the quality of DST was comprehensively and systematically evaluated. Abstract : An offline two‐dimensional LC‐MS method was developed to systematically characterize Dioscorea septemloba Thunb . Characterization of differential components in DST from different habitats was done by using the metabolomics method based on DIA analysis. Six significantly differential compounds were quantified by UPLC‐MS/MS, which could provide a certain reference for quality control of DST.